Vibration fatigue properties of laminated and 2.5D woven composites: A comparative study. (March 2023) - Wang, Yana; Gong, Yu; Zhang, Qin; He, Yuhuai; Jiao, Jian; Hu, Ning
Highlights: Vibration fatigue tests are conducted on cantilever beam specimens made of novel 2.5D woven and laminated composites. The ε- N curves, strain fatigue limits, mechanical properties, and internal micro damage modes are obtained. Variation laws of the normalized resonance frequencies ( f / f 0 ) versus the number of cycles N are revealed. The vibration fatigue behaviors of the laminated and 2.5D woven composites are comprehensively compared. Abstract: Laminated and 2.5D woven composites are the two main configurations for CFRP used in turbofan engine blades. However, vibration fatigue behaviors of both structures and their differences are still lacking investigation. In this study, resonance fatigue tests based on the first-order cantilever beam bending are performed under eight strain levels on the laminated and 2.5D woven T800/epoxy composites with special angle-interlock architecture. Parameters related to the vibration fatigue behaviors, such as the variations of the normalized resonance frequency with the number of fatigue cycles, the retention rate of the load capacity, and the stiffness of the laminated and 2.5D woven composites are obtained and compared. The mathematical expressions of the ε - N curves for the two materials under the first-order resonant bending fatigue tests are obtained, and the strain limit values of the laminated and 2.5D woven composites that can withstand 10 7 cycles are estimated to be about 5000 με and 2400 με respectively, which can be used for guiding the design of aeroengine blades. Besides, the damage mechanisms of both materials are revealed by X-ray Micro CT. The main damage mode of the laminated structures is delamination, which is prone to unstable crack propagation. However, the damage propagation within the 2.5D woven structures exhibits multiple paths as a result of the warp yarns interlocked in the thickness direction. By comparing the vibration fatigue behavior and test data of these two materials, it can be concluded that the design limit for the vibration fatigue strain level of the laminated structures is higher than that of woven structures, but the damage resistance of the woven structures is better than laminated structures.